MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS MAHASISWA MELALUI TUGAS JURNAL BELAJAR MATA KULIAH EVALUASI PEMBELAJARAN - Prasetiyo, Totok Hari; Jannah, Iis Ni’matul (Nusantara Hasana Journal, 2021)
This research is motivated by the low critical thinking skills of students with an average value of 60.58. Students tend not to assess learning patterns and strategies so students also do not have plans to make improvements to the way of learning to deal with further learning. This study aims to improve students' critical thinking skills after being given an action in the form of a learning journal assignment. The stages are in the form of planning, implementation, and reflection cycles. If the first cycle has not been achieved in accordance with the targeted increase, then continued with the second cycle. The results showed a significant increase from before being subjected to action by 60.58 increased in the first cycle of 71.63 and increased beyond the target of 78.43. Theoretically the increase in critical thinking skills is due to the character of the learning journal task that can develop academic abilities, and be able to express feelings, thoughts and expectations about learning.